The Influence of Aggressive Parenteral Nutrition to Preterm and Very Low Birth Weight Infants. (19th January 2015) - Liu, Ming-Yi; Chen, Yi-Yin; Hu, Shu-Hui; Chen, Yu-Kuei; Chang, Sue-Joan
Background . To achieve the weight gain of preterm infants who are appropriate for gestational age without adverse effect, there should be no interruption in delivery of nutrients from time of birth. Methods . Twenty-eight very low birth weight infants were eligible for the study. Those administered conventional nutrition (amino acids 2 g/kg/day started on third day of life) were classified as the conventional support (CVS) group, and those administered aggressive early nutrition (amino acid 2 g/kg/day started on first day of life) were classified as the aggressive support (AGS) group. Results . The days babies took to reach the weight of 2000 g in the AGS group was significantly shorter than for babies in the CVS group, and babies in the AGS group showed better tolerance to enteral nutrition and had shortened neonatal intensive care unit days. Conclusion . The results demonstrated that aggressive early nutrition showed better tolerance to enteral nutrition, higher total calories, and shortened the stay in the neonatal intensive care unit.